The Effects of Colour in Work Environment: A systematic review - Nattha Savavibool; Birgitta Gatersleben; Chumporn Moorapun (My University, 2018)
In the work environment, colour is considered an important design element used to improve aesthetic qualities of the environment and for a company’s branding. This paper reviews existing research on the effects of workplace colour on worker’s mood, wellbeing and other work-related outcomes. In total 40 papers fitted the inclusion criteria and were included in the review. The results show a significant influence of colour on affect (e.g. mood, emotion), wellbeing (e.g. stress, comfort, wellbeing), and performance (e.g. productivity, performance, creativity). The review concludes with suggestions for further research.Keywords: Colour perception; Colour psychology; Effect of colour; Work environment.eISSN 2398-4295 © 2018. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open-access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: http://dx.doi.org/10.21834/ajbes.v3i13.152
Keywords: Color perception and design